Variation of air condition parameters, in the conditions of the presence of carbon dioxide, in the duct of ventilation installations - Cămărășescu Alexandru; Drăgoescu Răzvan (MATEC Web of Conferences, 2024)
Industrial ventilation takes into account the quality of the air inside the IAQ (Indoor Air Quality) and the degree of exposure of workers. In industrial targets the emission regime of contaminants can be 10–100 times higher than in non-industrial targets, but for many pollutants the IAQ levels can be the same. The parameters of the state of the air which are of interest for the technique of ventilation and air conditioning are: air temperature and humidity, atmospheric pressure and air speed. For the study on the variation of the air state parameters inside the industrial ventilation installations, in the experiment laboratory, on the study of the industrial ventilation systems, the experiment was performed on the variation of the air state parameters in the conditions of circulation through the ventilation duct. an amount of carbon dioxide. Prior to the introduction of carbon dioxide into the duct, the ventilation system was started, at nominal parameters. During the experiment, the operating parameters of the drive motor were changed using a frequency converter on levels 50; 40; 30; 20; 10 and 5 Hz. The ventilation system used was structured by means of flow converters which were fixed in the open position. The ventilation system as well as the flow variators were operated by the SCADA type command and control system The paper will present the analysis of the variation of state parameters (temperature, humidity, absolute pressure and air speed) by introducing a constant amount of carbon dioxide in the ventilation duct.